Regional Input-Output tables in India : A Survey - Planning Commission (Planning Commission, 1982)
This survey examines the development, structure, and applications of regional input-output tables in India, highlighting their importance in understanding intersectoral linkages and informing economic planning. Since the Third Five Year Plan, these tables have been crucial for assessing regional disparities and guiding policy interventions. Despite progress, variability in methodologies, sectoral coverage, and data quality—especially in agriculture and unorganized industries—limits their effectiveness. The study emphasizes the need for standardization, improved data collection, and integration with national planning models. Adoption of advanced techniques such as RAS and Generalized Inverse methods is recommended to enhance reliability and support informed regional development strategies.
Government of India Planning Commission (UNDP Transport Policy Planning Project)
Government of India Planning Commission (UNDP Transport Policy Planning Project)
Keywords: Output Tables; India; Economic Planning; Sectoral Interdependence; Regional Development; Data Standardization; Methodology; Agricultural Data; Planning Commission; Regional Disparities